All-solid secondary battery

The all-solid-state battery design addresses internal stress and moisture issues by optimizing porosity ratios and void diameters in its layers, enhancing cycle and high-humidity performance.

JP7608324B2Active Publication Date: 2025-01-06TDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021505048
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-08
Filing Date
2020-03-06
Publication Date
2025-01-06
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

All-solid-state batteries face issues with internal stress and cycle characteristics due to volumetric expansion and contraction of electrode layers during charging and discharging, particularly under high temperature and high humidity conditions, leading to potential cracks and moisture infiltration that degrade performance.

Method used

The battery design incorporates a specific porosity ratio and average void diameter in the side margin and solid electrolyte layers, ensuring balanced volumetric expansion and contraction, thereby reducing internal resistance and preventing moisture ingress.

Benefits of technology

The design achieves improved cycle characteristics and high-temperature, high-humidity performance by maintaining structural integrity and enhancing adhesion between electrode layers and electrolyte, resulting in stable battery operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608324000009
    Figure 0007608324000009
  • Figure 0007608324000010
    Figure 0007608324000010
  • Figure 0007608324000001
    Figure 0007608324000001
Patent Text Reader

Abstract

This all solid state secondary battery comprises positive electrode layers, negative electrode layers, solid electrolyte layers, and side margin layers disposed at the outer periphery of each positive electrode layer and negative electrode layer and aligned therewith, wherein the positive electrode layers and the side margin layers disposed at the outer periphery thereof, and the negative electrode layers and the side margin layers disposed at the outer periphery thereof are stacked alternately, with the solid electrolyte layers interposed therebetween, to form a stacked body, and if the porosity of the side margin layers is φm and the porosity of the solid electrolyte layers is φe, a porosity ratio (φm / φe) satisfies formula (1). (1) ... 0.5≤(φm / φe)<1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state secondary battery. This application claims priority based on Japanese Patent Application No. 2019-043162 filed in Japan on March 8, 2019, and Japanese Patent Application No. 2019-043163 filed in Japan on March 8, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, electronics technology has developed remarkably, and portable electronic devices are being made smaller, lighter, thinner, and more multifunctional. Accordingly, there is a strong demand for batteries that serve as the power source for electronic devices to be smaller, lighter, thinner, and more reliable. Currently, lithium ion secondary batteries are widely used, and electrolytes (electrolytic solutions) such as organic solvents have been used as a medium for transferring ions. However, there is a risk of leakage of the electrolyte in batteries with the above configuration.

[0003] In addition, since the organic solvents used in the electrolyte are flammable substances, it is necessary to further improve the safety of the battery. Therefore, one measure to improve the safety of the battery is to use a solid electrolyte instead of the electrolyte. Furthermore, the development of an all-solid-state battery in which a solid electrolyte is used as the electrolyte and other components are also solid is being promoted.

[0004] For example, Patent Document 1 proposes an all-solid-state lithium secondary battery in which all components are solid, using a non-flammable solid electrolyte. This laminate for an all-solid-state lithium secondary battery includes an active material layer and a solid electrolyte layer sinter-bonded to the active material layer, the active material layer including a crystalline first material capable of releasing and absorbing lithium ions, and the solid electrolyte layer including a crystalline second material having lithium ion conductivity. Patent Document 1 states that the filling rate of the solid electrolyte layer is preferably more than 70%.

[0005] On the other hand, Patent Document 2 describes a lithium ion conductive solid electrolyte that is produced by sintering a molded body containing inorganic powder and has a porosity of 10 vol % or less.

[0006] As described in Patent Documents 1 and 2, it is generally considered preferable that the solid electrolyte constituting the all-solid-state battery is dense. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2007-5279 A [Patent Document 2] JP 2007-294429 A [Patent Document 3] International Publication No. 2013 / 175993 [Patent Document 4] International Publication No. 2008 / 059987 Summary of the Invention [Problem to be solved by the invention]

[0008] However, as described in Patent Documents 1 and 2, in an all-solid-state battery with a densified solid electrolyte layer, internal stress may be concentrated in the solid electrolyte layer due to shrinkage during firing when manufacturing the all-solid-state battery, or due to volumetric expansion and contraction of the electrode layer that occurs during charging and discharging of the all-solid-state battery, causing cracks in some cases. As a result, it was found that the internal resistance increases and the cycle characteristics deteriorate.

[0009] In response to such problems, Patent Document 3 describes a solid electrolyte layer in which a portion with low porosity is formed in a region close to the electrode layer of the solid electrolyte layer, and a portion with high porosity is formed in a region away from the electrode layer. However, the inventors' investigations have found that when portions with high and low porosity are formed in the solid electrolyte layer as in Patent Document 3, the internal resistance of the solid electrolyte layer increases instead, and sufficient cycle characteristics cannot be obtained.

[0010] Furthermore, all-solid-state batteries, in which all components are made of solids, have the problem of internal stress caused by the volumetric expansion and contraction of the electrode layers that occurs during charging and discharging, but little research has been done into how this problem affects the characteristics in high-temperature, high-humidity environments.

[0011] As mentioned above, Patent Document 3 proposes a structure in which the porosity of the solid electrolyte layer close to the electrode layer is reduced and the porosity of the solid electrolyte layer away from the electrode layer is increased to relieve the internal stress caused by the volumetric expansion and contraction of the electrode layer during charging and discharging. However, no consideration is given to the characteristics in a high-temperature and high-humidity environment. Patent Document 4 proposes a structure in which a porous layer is provided near the electrode layer in the solid electrolyte layer to relieve internal stress caused by the volumetric expansion and contraction of the electrode layer during charging and discharging, but does not consider the characteristics in a high-temperature, high-humidity environment.

[0012] When a porous layer is provided in the solid electrolyte layer or the porosity is increased in part of the solid electrolyte layer as proposed in Patent Documents 3 and 4, there is a concern that moisture may penetrate into the laminate, more specifically into the solid electrolyte layer that is located between the positive electrode layer and the negative electrode layer and contributes to the exchange of lithium ions, during the expansion and contraction process during charging and discharging under high temperature and high humidity conditions, resulting in deterioration of the high temperature and high humidity resistance cycle characteristics.

[0013] An object of the present invention is to provide an all-solid-state secondary battery having good cycle characteristics, or an all-solid-state secondary battery having good high-temperature and high-humidity resistance cycle characteristics. [Means for solving the problem]

[0014] In order to solve the above problems, the present invention provides the following means.

[0015] [First aspect] (1) An all-solid-state secondary battery according to a first aspect of the present invention includes a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer, a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer, a solid electrolyte layer including a solid electrolyte, and a side margin layer arranged adjacent to and on the outer periphery of the positive electrode layer and the negative electrode layer, respectively, wherein the positive electrode layer and the side margin layer arranged on the outer periphery thereof, and the negative electrode layer and the side margin layer arranged on the outer periphery thereof are alternately stacked via the solid electrolyte layer to form a laminate, and the porosity of the side margin layer is set to φ m , the porosity of the solid electrolyte layer is φ e When the void ratio (φ m / φ e ) satisfies the following formula (1): 0.5≦(φ m / φ e )<1.0 ···· (1)

[0016] (2) The all-solid-state secondary battery according to (1) is characterized in that the porosity ratio (φ m / φ e ) may satisfy the following formula (2): 0.6≦(φ m / φ e )<1.0 ···· (2)

[0017] (3) The all-solid-state secondary battery according to either (1) or (2) has a porosity φ of the solid electrolyte layer. e is 1.0%≦φ e It may be ≦25.0%.

[0018] (4) In the all-solid-state secondary battery according to any one of (1) to (3), the average circular area equivalent diameter d of the voids included in the solid electrolyte layer and the side margin layer may be 0.1≦d<2.0 μm; Here, the average circular area equivalent diameter d is calculated by the following formula (3) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1 / 2) ×2 (3) It is calculated as follows.

[0019] [Second mode] (5) An all-solid-state secondary battery according to a second aspect of the present invention includes a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer, a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer, a solid electrolyte layer including a solid electrolyte, and a side margin layer arranged adjacent to and on the outer periphery of the positive electrode layer and the negative electrode layer, respectively, wherein the positive electrode layer and the side margin layer arranged on the outer periphery thereof, and the negative electrode layer and the side margin layer arranged on the outer periphery thereof are alternately stacked via the solid electrolyte layer to form a laminate, and the porosity of the side margin layer is set to φ m , the porosity of the solid electrolyte layer is φ e When the void ratio (φ m / φ e ) satisfies the following formula (1): 1.0<(φ m / φ e )≦4.0 (4)

[0020] (6) The all-solid-state secondary battery according to (5) has a porosity φ of the side margin layer. m is 0.1%≦φ m It may be ≦20.0%.

[0021] (7) In the all-solid-state secondary battery according to any one of (5) and (6), an average circular area equivalent diameter d of voids included in the solid electrolyte layer and the side margin layer may be 0.05≦d≦2.00 μm; Here, the average circular area equivalent diameter d is calculated by the following formula (3) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1 / 2) ×2 (3) It is calculated as follows. Effect of the Invention

[0022] According to the present invention, it is possible to provide an all-solid-state secondary battery having good cycle characteristics, or an all-solid-state secondary battery having good high-temperature and high-humidity resistance cycle characteristics. [Brief description of the drawings]

[0023] [Figure 1]FIG. 1 is a schematic cross-sectional view of an all-solid-state secondary battery according to a first or second embodiment. [Diagram 2] FIG. 2 is a perspective view showing a schematic view for explaining the shape of a side margin layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the first and second embodiments of the present invention will be described in detail with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics of the first and second embodiments easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present embodiment is not limited to them. They can be modified as appropriate within the scope of the effects of the present invention.

[0025] Examples of all-solid-state secondary batteries include all-solid-state lithium ion secondary batteries, all-solid-state sodium ion secondary batteries, all-solid-state magnesium ion secondary batteries, etc. In the following, an all-solid-state lithium ion secondary battery will be described as an example, but the first embodiment or the second embodiment can be generally applied to all-solid-state secondary batteries.

[0026] FIG. 1 is an enlarged schematic cross-sectional view of a main part of an all-solid-state lithium-ion secondary battery according to the first or second embodiment. The all-solid-state lithium-ion secondary battery shown in FIG. 1 includes a laminate having a first electrode layer, a second electrode layer, and a solid electrolyte layer. Hereinafter, one of the first electrode layer and the second electrode layer functions as a positive electrode, and the other functions as a negative electrode. The positive and negative polarities of the electrode layers change depending on which polarity is connected to the external terminal. In the following, for ease of understanding, the first electrode layer will be described as a positive electrode layer, and the second electrode layer will be described as a negative electrode layer.

[0027] [First embodiment] The all-solid-state lithium-ion secondary battery 100 has a positive electrode layer 1 including a positive electrode collector layer 1A and a positive electrode active material layer 1B, a negative electrode layer 2 including a negative electrode collector layer 2A and a negative electrode active material layer 2B, a solid electrolyte layer 3 including a solid electrolyte, and side margin layers 41, 42 arranged adjacent to and on the outer periphery of the positive electrode layer 1 and the negative electrode layer 2, respectively, and forms a laminate 20 in which the positive electrode layer 1 and the side margin layer 41 arranged on its outer periphery, and the negative electrode layer 2 and the side margin layer 42 arranged on its outer periphery are alternately stacked via the solid electrolyte layer 3.

[0028] The positive electrode layers 1 (first electrode layers) are each connected to a first external terminal 6, and the negative electrode layers 2 (second electrode layers) are each connected to a second external terminal 7. The first external terminal 6 and the second external terminal 7 are electrical contacts with the outside. In FIG. 1, the direction perpendicular to the paper surface is the X direction, the direction in which the first external terminal 6 and the second external terminal 7 face each other is the Y direction, and the stacking direction is the Z direction.

[0029] (Laminate) The laminate 20 includes a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3, and side margin layers 41 and .

[0030] In the laminate 20, the positive electrode layers 1 and the negative electrode layers 2 are alternately laminated with a solid electrolyte layer 3 (more specifically, an interlayer solid electrolyte layer 3A) interposed therebetween. The all-solid-state lithium-ion secondary battery 100 is charged and discharged by the exchange of lithium ions between the positive electrode layers 1 and the negative electrode layers 2 via the solid electrolyte layer 3. The number of stacked positive electrode layers 1 and negative electrode layers 2 is not particularly limited, but the total number of positive electrode layers 1 and negative electrode layers 2 is generally in the range of 10 to 200 layers, and preferably in the range of 20 to 100 layers.

[0031] (Positive and negative electrode layers) The positive electrode layer 1 has a positive electrode current collector 1A and a positive electrode active material layer 1B containing a positive electrode active material. The negative electrode layer 2 has a negative electrode current collector 2A and a negative electrode active material layer 2B containing a negative electrode active material.

[0032] The positive electrode current collector 1A and the negative electrode current collector 2A are made of at least one material having high electrical conductivity. Examples of the material having high electrical conductivity include metals or alloys containing at least one metal element selected from silver (Ag), palladium (Pd), gold (Au), platinum (Pt), aluminum (Al), copper (Cu), and nickel (Ni), and nonmetals such as carbon (C). Among these metal elements, copper and nickel are preferable in consideration of the manufacturing cost in addition to the high electrical conductivity. Furthermore, copper is difficult to react with the positive electrode active material, the negative electrode active material, and the solid electrolyte. Therefore, when copper is used for the positive electrode current collector 1A and the negative electrode current collector 2A, the internal resistance of the all-solid-state lithium-ion secondary battery 100 can be reduced. The materials constituting the positive electrode current collector 1A and the negative electrode current collector 2A may be the same or different. The thicknesses of the positive electrode current collector 1A and the negative electrode current collector 2A are not limited, but as a guideline, they are in the range of 0.5 μm to 30 μm.

[0033] The positive electrode active material layer 1B is formed on one or both sides of the positive electrode collector 1A. For example, the positive electrode layer 1 located at the top of the stacking direction of the all-solid-state lithium-ion secondary battery 100 does not have the negative electrode layer 2 facing it on the upper side of the stacking direction. Therefore, in the positive electrode layer 1 located at the top of the all-solid-state lithium-ion secondary battery 100, the positive electrode active material layer 1B may be formed only on one side of the lower side of the stacking direction, but there is no particular problem even if it is formed on both sides. The negative electrode active material layer 2B is also formed on one or both sides of the negative electrode collector 2A, similar to the positive electrode active material layer 1B. The thickness of the positive electrode active material layer 1B and the negative electrode active material layer 2B is preferably in the range of 0.5 μm to 5.0 μm. By making the thickness of the positive electrode active material layer 1B and the negative electrode active material layer 2B 0.5 μm or more, the electric capacity of the all-solid-state lithium ion secondary battery can be increased, while by making the thickness 5.0 μm or less, the diffusion distance of lithium ions is shortened, and therefore the internal resistance of the all-solid-state lithium ion secondary battery can be further reduced.

[0034] The positive electrode active material layer 1B and the negative electrode active material layer 2B each contain a positive electrode active material or a negative electrode active material that donates and receives electrons to and from lithium ions. The positive electrode active material layer 1B and the negative electrode active material layer 2B may further contain a conductive assistant, etc. It is preferable that the positive electrode active material and the negative electrode active material can efficiently insert and extract lithium ions.

[0035] There is no clear distinction between the active materials constituting the positive electrode active material layer 1B and the negative electrode active material layer 2B, and by comparing the potentials of two types of compounds, a compound showing a more noble potential can be used as the positive electrode active material, and a compound showing a more base potential can be used as the negative electrode active material. Therefore, the active materials will be collectively described below.

[0036] The active material may be a transition metal oxide, a transition metal composite oxide, or the like. For example, the transition metal oxide or transition metal composite oxide may be a lithium manganese composite oxide, Li 2 Mn a Ma 1-a O 3 (0.8≦a≦1, Ma=Co, Ni), lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Lithium Manganese Spinel (LiMn 2 O 4 ), general formula: LiNi x Co y Mn z O 2 A composite metal oxide represented by (x+y+z=1, 0≦x≦1, 0≦y≦1, 0≦z≦1), a lithium vanadium compound (LiV 2 O 5 ), olivine-type compound LiM b PO 4 (However, M b is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, and Zr), lithium vanadium phosphate (Li 3 V 2 (PO 4 ) 3 or LiVOPO 4 ), pyrophosphate compound Li 1+X F e P 2O 7 (0 ≦ x ≦ 1), Li 1-X VP 2 O 7 (0 ≦ x < 1), Li 2 M d P 2 O 7 (M d = Mn, Co, Fe, Ni), Li 2 MnO 3 - LiM c O 2 (M c = Mn, Co, Ni) represented by a Li-excess solid solution cathode, lithium titanate (Li 4 Ti 5 O 12 ), Li s Ni t Co u Al v O 2 (0.9 < s < 1.3, 0.9 < t + u + v < 1.1) represented by a composite metal oxide, etc. can be mentioned.

[0037] The positive electrode current collector 1A and the negative electrode current collector 2A may each contain a positive electrode active material and a negative electrode active material. The content ratio of the active material contained in each current collector is not particularly limited as long as it functions as a current collector. For example, it is preferable that the positive electrode current collector / positive electrode active material, or the negative electrode current collector / negative electrode active material is in the range of 90 / 10 to 70 / 30 in volume ratio.

[0038] When the positive electrode current collector 1A and the negative electrode current collector 2A each contain a positive electrode active material and a negative electrode active material, the adhesion between the positive electrode current collector 1A and the positive electrode active material layer 1B and between the negative electrode current collector 2A and the negative electrode active material layer 2B is improved.

[0039] (Solid electrolyte layer) As shown in FIG. 1, the solid electrolyte layer 3 has an interlayer solid electrolyte layer 3A located between the positive electrode active material layer 1B and the negative electrode active material layer 2B. The solid electrolyte layer 3 may further include an outermost solid electrolyte layer 3B located outside either one or both of the positive electrode layer 1 (positive electrode current collector 1A) and the negative electrode layer 2 (negative electrode current collector 2A) (both in FIG. 1). Here, the "outside" refers to the outside of the positive electrode layer 1 or the negative electrode layer 2 that is closest to the surfaces 5A, 5B of the laminate 20. The solid electrolyte layer 3 does not necessarily have to have the outermost solid electrolyte layer 3B. In this case, the surfaces 5A, 5B of the laminate 20 become the positive electrode layer 1 or the negative electrode layer 2.

[0040] It is preferable to use a material having low electronic conductivity and high lithium ion conductivity for the solid electrolyte layer 3. The solid electrolyte is, for example, La 0.5 Li 0.5 TiO 3 Perovskite compounds such as Li 14 Zn(GeO 4 ) 4 Lithium-type compounds such as Li 7 La 3 Zr 2 O 12 Garnet-type compounds such as Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Or Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , LiZr 2 (PO 4 ) 3 Nasicon-type compounds such as Li 3.25 Ge 0.25 P 0.75 S 4 Or Li 3 P.S. 4 Thiolicicon-type compounds such as Li 2 SP 2 S 5 Or Li 2 O.V. 2 O 5 -SiO 2 Glass compounds such as Li 3 PO 4 Or Li 3.5 S0.5 P 0.5 O 4 Or Li 2.9 PO 3.3 N 0.46 and the like.

[0041] In addition, it is preferable to select the solid electrolyte layer 3 in accordance with the active materials used in the positive electrode layer 1 and the negative electrode layer 2. For example, it is more preferable that the solid electrolyte layer 3 contains the same elements as the elements constituting the active materials. When the solid electrolyte layer 3 contains the same elements as the elements constituting the active materials, the bonding at the interfaces between the positive electrode active material layer 1B and the negative electrode active material layer 2B and the solid electrolyte layer 3 becomes strong. In addition, the contact area at the interfaces between the positive electrode active material layer 1B and the negative electrode active material layer 2B and the solid electrolyte layer 3 can be increased.

[0042] The thickness of the interlayer solid electrolyte layer 3A is preferably in the range of 0.5 μm to 20.0 μm. By making the thickness of the interlayer solid electrolyte layer 3A 0.5 μm or more, it is possible to reliably prevent a short circuit between the positive electrode layer 1 and the negative electrode layer 2, and by making the thickness 20.0 μm or less, the migration distance of lithium ions is shortened, thereby further reducing the internal resistance of the all-solid-state lithium ion secondary battery.

[0043] The thickness of the outermost solid electrolyte layer 3B is not particularly limited, but is preferably 20 μm or more and 100 μm or less, for example, as a guideline. When the thickness is 20 μm or more, the positive electrode layer 1 or the negative electrode layer 2 closest to the surface 5A, 5B of the laminate 20 is less likely to be oxidized due to the influence of the atmosphere in the firing process, resulting in an all-solid-state lithium-ion secondary battery with high capacity. In addition, when the thickness is 100 μm or less, sufficient moisture resistance is ensured even in a high-temperature and high-humidity environment, resulting in an all-solid-state lithium-ion secondary battery with high reliability and high volumetric energy density.

[0044] (Side margin layer) 1, the laminate 20 includes a solid electrolyte and includes side margin layers 41, 42 arranged adjacent to and around the outer periphery of the positive electrode layer 1 and the negative electrode layer 2. The side margin layers 41, 42 may be referred to as a positive electrode side margin layer and a negative electrode side margin layer, respectively. FIG. 1 shows an example in which the solid electrolyte contained in the side margin layers 41 and 42 is the same as the solid electrolyte contained in the solid electrolyte layer 3, but they may be different. The side margin layers 41, 42 are preferably provided to eliminate the step between the interlayer solid electrolyte layer 3A and the positive electrode layer 1, and the step between the interlayer solid electrolyte layer 3A and the negative electrode layer 2. Therefore, the side margin layers 41, 42 are formed in the main surface of the solid electrolyte layer 3 in an area other than the positive electrode layer 1 and the negative electrode layer 2, at substantially the same height as the positive electrode layer 1 or the negative electrode layer 2 (i.e., arranged alongside the positive electrode layer 1 and the negative electrode layer 2, respectively). The presence of the side margin layers 41, 42 eliminates the step between the solid electrolyte layer 3 and the positive electrode layer 1, and between the solid electrolyte layer 3 and the negative electrode layer 2, so that the density of the solid electrolyte layer 3 and each electrode layer is increased, and delamination and warping due to firing of the all-solid-state battery are less likely to occur.

[0045] FIG. 2 is a perspective view showing a schematic diagram of only one solid electrolyte layer 3 and one adjacent negative electrode layer 2 and negative electrode side margin layer 42 in order to explain the shape of the side margin layer. The negative electrode side margin layer 42 shown in FIG. 2 is disposed in contact with the outer peripheral side surface 2b, the outer peripheral side surface 2c, and the outer peripheral side surface 2d, other than the outer peripheral side surface 2a on the second external terminal 7 (see FIG. 1), among the outer peripheral (outer peripheral side surface) of the negative electrode layer 2, which is rectangular in plan view from the Z direction. That is, the side margin layer 42 is composed of a portion 42A disposed in contact with the outer peripheral side surface 2b, and a portion 42B disposed in contact with each of the outer peripheral side surfaces 2c and 2d. In FIG. 2, for convenience, the portion 42A and the portion 42B are separately indicated by dotted lines and are given reference numerals. The portion 42A is only the portion disposed in contact with the outer peripheral side surface 2b, and the portion 42B is composed of 42Ba, which is a combination of a portion disposed in contact with the outer peripheral side surface 2c and a portion disposed in contact with one end surface of the portion 42A, and 42Bb, which is a combination of a portion disposed in contact with the outer peripheral side surface 2d and a portion disposed in contact with the other end surface of the portion 42A.

[0046] 2 has a shape (U-shape) in which a part of the side margin layer is disposed on the outer peripheral side surface other than the second external terminal side, but the side margin layer may be composed of only a portion (corresponding to portion 42A in FIG. 2) that contacts the outer peripheral side surface on the opposite side of the external terminal. In this case, since the electrode layer is exposed on the side surface of the laminate, it is preferable to cover it with a protective layer to be described later so as to prevent exposure.

[0047] The material constituting the side margin layers 41 and 42 is not particularly limited, but preferably contains a material that has a thermal contraction behavior similar to that of the solid electrolyte 3 in the firing process described below. For example, when the solid electrolyte 3 is lithium titanium aluminum phosphate Li 1+x Al x Ti 2-x (PO 4 ) 3 If (0≦x≦0.6), the side margin layers 41 and 42 are also made of lithium titanium aluminum phosphate Li 1+x Al x Ti 2-x (PO 4 ) 3(0≦x≦0.6). Since the solid electrolyte 3 and the side margin layers 41, 42 are made of the same material, cracks due to differences in thermal contraction are unlikely to occur, and the interfacial bonding between the solid electrolyte 3 and the side margin layers 41, 42 is good. The side margin layers 41, 42 may contain a material other than a solid electrolyte. Examples of materials constituting the side margin layers 41, 42 include the active material constituting the positive electrode active material 1B or the negative electrode active material layer 2B, and a glass material (Bi 2 O 3 , SiO 2 , B 2 O 3 , ZnO, etc.)

[0048] <Porosity> In this specification, the term "void ratio" refers to the ratio, expressed as a percentage (%), of the total area of ​​void portions to the total area of ​​a given layer in an image of a cross section of a laminate parallel to the lamination direction. The porosity shown in the examples was calculated, for example, by the following method. The laminate was cut parallel to the lamination direction with a cross-section polisher (CP) and the cross section was observed with a scanning electron microscope (SEM). Ten cross sections including the side margin layer were observed in a 1000x observation image, and the porosity of the side margin layer was calculated for each SEM image obtained using image processing software. The side margin layer in the SEM image was extracted by trimming, converted into a monochrome image and binarized, and the number of pixels was calculated by coloring the gap part black and the other part white. The number of pixels of the extracted side margin layer was calculated by adding up the number of pixels of the gap part and the other part. The porosity of the side margin layer was then calculated by the following formula. Porosity of side margin layer (%) = Number of pixels in void area ÷ (Number of pixels in void area and other areas) × 100% The average value of the porosity obtained from the SEM images at 10 points was taken as the porosity of the side margin layer. The porosity of the solid electrolyte layer was also calculated by extracting the solid electrolyte layer in the SEM image by trimming it, and calculating the porosity of the solid electrolyte layer in the same manner as the calculation of the porosity of the side margin layer. The 10 observation points may be obtained within the same cross section, or may be obtained from cross sections of different laminates within the same lot.

[0049] In the first embodiment, the porosity of the side margin layers 41 and 42 is set to φ m , the porosity of the solid electrolyte layer 3 is φ e When the void ratio (φ m / φ e ) satisfies the following formula (1); 0.5≦(φ m / φ e )<1.0 ···· (1)

[0050] The reason why excellent cycle characteristics are obtained when the relationship as in formula (1) is satisfied is believed to be as follows. The electrode layers (positive electrode layer 1, negative electrode layer 2) which expand and contract in volume are sandwiched between solid electrolyte layers 3 from the upper and lower surfaces, and side margin layers 41 and 42 are formed on the outer periphery. The porosity φ of the side margin layers 41 and 42 m and the porosity φ of the solid electrolyte layer 3 e However, (φ m / φ e ) < 1, that is, the porosity φ of the side margin layers 41 and 42 m is the porosity φ of the solid electrolyte layer 3 e When the porosity φ of the side margin layers 41 and 42 is smaller than φ, the volume expansion of the electrode layers occurs preferentially on the solid electrolyte side located above and below. This volume expansion enhances the adhesion between the electrode layers (positive electrode layer 1, negative electrode layer 2) and the solid electrolyte layer 3 that sandwiches the electrode layers. As a result, the internal resistance decreases, and better cycle characteristics are obtained. On the other hand, when the porosity φ of the side margin layers 41 and 42 is smaller than φ, the volume expansion of the electrode layers occurs preferentially on the solid electrolyte side located above and below. This volume expansion enhances the adhesion between the electrode layers (positive electrode layer 1, negative electrode layer 2) and the solid electrolyte layer 3 that sandwiches the electrode layers. As a result, the internal resistance decreases, and better cycle characteristics are obtained. m is the porosity φ of the solid electrolyte layer 3 e If φ is equal to m is φ eIf the difference is larger than 100%, the volume expansion of the electrode layer occurs preferentially on the side margin layer side of the outer periphery. Therefore, the adhesion between the electrode layer (positive electrode layer 1, negative electrode layer 2) and the solid electrolyte layer 3 is not improved. As a result, the internal resistance does not decrease, and the cycle characteristics are likely to decrease. (φ m / φ e When the ratio is less than 0.5, the volume expansion of the active material layer occurs preferentially in the solid electrolyte layer rather than in the side margin layer, but this occurs excessively, so that cracks tend to occur inside the all-solid-state battery, and it becomes difficult to obtain excellent cycle characteristics.

[0051] In the first embodiment, the porosity ratio (φ m / φ e ) more preferably satisfies the following formula (2): 0.6≦(φ m / φ e )<1.0 ···· (2) 0.6≦(φ m / φ e ), the result is an all-solid-state secondary battery that exhibits high cycle characteristics.

[0052] In the first embodiment, the porosity φ of the solid electrolyte layer 3 e 1.0%≦φ e It is preferable that it is ≦25.0%. Porosity φ of solid electrolyte layer 3 e When this range is satisfied, better cycle characteristics can be obtained.

[0053] <Average circular area equivalent diameter of voids> In the first embodiment, the average circular area equivalent diameter (diameter) d of the voids contained in the solid electrolyte layer 3 and the side margin layers 41, 42 preferably satisfies 0.1≦d<2.0 μm. Here, the average circular area equivalent diameter d is calculated by the following formula (2) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1 / 2) ×2 (3) It is calculated as follows. Here, n is preferably a number that does not cause large variations in the average equivalent circular area diameter depending on how the voids are selected. For example, as in the embodiment, n may be set to 20. In this case, when the number of voids in the SEM image is less than 20, the total area of ​​all the voids is taken as X.

[0054] In the first embodiment, when the average circular area equivalent diameter d of the voids is 0.1≦d<2.0 μm, the cycle characteristics are more excellent. If it is 2.0 μm or more, cracks are likely to occur in the solid electrolyte layer and the side margin layer due to volume expansion and contraction caused by the charge and discharge reaction, and the cycle characteristics may deteriorate.

[0055] The average circular area equivalent diameter in the examples was calculated by converting the SEM images of the solid electrolyte layer and the side margin layer into monochrome images and binarizing them using the method used to calculate the porosity described above, obtaining the total area X of a total of 20 void portions (black), and then using formula (3).

[0056] (Terminal) It is preferable to use a material with high electrical conductivity for the first external terminal 6 and the second external terminal 7 of the all-solid-state lithium-ion secondary battery 100. For example, silver (Ag), gold (Au), platinum (Pt), aluminum (Al), copper (Cu), tin (Sn), nickel (Ni), and chromium (Cr) can be used. The terminals may be single-layered or multi-layered.

[0057] (protective layer) The all-solid-state lithium-ion secondary battery 100 may also have a protective layer (not shown) on the outer periphery of the laminate 20 for electrically, physically, and chemically protecting the laminate 20 and the terminals. The material constituting the protective layer is preferably excellent in insulation, durability, and moisture resistance, and is environmentally safe. For example, it is preferable to use glass, ceramics, thermosetting resin, or photocurable resin. The protective layer may be made of one type of material, or a combination of two or more types of materials. The protective layer may be a single layer, but it is preferable to have a plurality of layers. Among them, an organic-inorganic hybrid in which a thermosetting resin and ceramic powder are mixed is particularly preferable.

[0058] (Manufacturing method of all-solid-state lithium-ion secondary battery) The all-solid-state lithium-ion secondary battery 100 may be manufactured by a co-firing method or a sequential firing method. The co-firing method is a method in which materials forming each layer are stacked and a laminate is manufactured by simultaneous firing. The sequential firing method is a method in which each layer is manufactured in order, and a firing step is inserted after each layer is manufactured. The co-firing method can reduce the number of work steps for the all-solid-state lithium-ion secondary battery 100. Furthermore, the co-firing method makes the obtained laminate 20 denser. The case in which the co-firing method is used will be described below as an example.

[0059] The co-firing method includes the steps of preparing a paste of each material that constitutes the laminate 20, applying and drying the paste to prepare a green sheet, stacking the green sheets, and co-firing the prepared laminate sheet.

[0060] First, the materials constituting the laminate 20, the positive electrode collector 1A, the positive electrode active material layer 1B, the solid electrolyte layer 3, the negative electrode active material layer 2B, the negative electrode collector 2A, and the side margin layers 41 and 42, are made into a paste.

[0061] The method of making the paste is not particularly limited. For example, the powder of each material is mixed with a vehicle to obtain a paste. Here, the vehicle is a general term for a medium in a liquid phase. The vehicle includes a solvent and a binder. By this method, a paste for the positive electrode collector 1A, a paste for the positive electrode active material layer 1B, a paste for the solid electrolyte layer 3, a paste for the negative electrode active material layer 2B, a paste for the negative electrode collector 2A, and a paste for the side margin layers 41 and 42 are prepared.

[0062] A known method can be used to change the porosity of the solid electrolyte layer 3 and the side margin layers 41 and 42. For example, the porosity can be controlled by including a void-forming agent in the paste and changing the content of the void-forming agent. The void-forming agent can be easily formed by burning off the void-forming agent by removing the binder or by firing the void-forming agent, or by dissolving the void-forming agent in water or a solvent. A material that does not ultimately remain as a residual component in the laminate is preferable, and it is preferable to use particles such as polymethylmethacrylate (PMMA), polyphenylene sulfide (PPS), styrene butadiene rubber (SBR), polyethylene (PE), polystyrene, polyamide (nylon), polyimide, polyamideimide, polyvinylidene fluoride, polyacrylic acid, calcium alginate, carbon, and protein. The particle size of the void-forming agent is preferably a fine particle shape, and the void size can be easily changed by suitably using a particle size of about 10 nm to 5 μm.

[0063] Next, a green sheet is prepared. The green sheet is obtained by applying the prepared paste onto a substrate such as PET (polyethylene terephthalate) in a desired order, drying as necessary, and then peeling off the substrate. The method of applying the paste is not particularly limited. For example, known methods such as screen printing, application, transfer, doctor blade, etc. can be adopted.

[0064] When producing the laminate 20, a positive electrode unit and a negative electrode unit described below are prepared, and the laminate can be produced.

[0065] First, the paste for the solid electrolyte layer 3 is formed into a sheet shape on a PET film by a doctor blade method, and then dried to form a solid electrolyte layer sheet. On the obtained solid electrolyte layer sheet, the paste for the positive electrode active material layer 1B is printed by screen printing and dried to form the positive electrode active material layer 1B.

[0066] Next, the paste for the positive electrode collector 1A is printed on the prepared positive electrode active material layer 1B by screen printing and dried to form the positive electrode collector 1A. Furthermore, the paste for the positive electrode active material layer 1B is printed again thereon by screen printing and dried. Then, the paste for the side margin layer is screen printed on the region of the solid electrolyte layer sheet other than the positive electrode layer and dried to form a side margin layer having approximately the same height as the positive electrode layer. Then, by peeling off the PET film, a positive electrode unit is obtained in which the positive electrode layer 1 and the side margin layer 41 are formed on the main surface of the solid electrolyte layer 3, in which the positive electrode active material layer 1B / positive electrode collector layer 1A / positive electrode active material layer 1B are laminated in this order.

[0067] By a similar procedure, a negative electrode unit is obtained in which the negative electrode layer 2, in which the negative electrode active material layer 2B / negative electrode current collector layer 2A / negative electrode active material layer 2B are laminated in this order, and the side margin layer 42 are formed on the main surface of the solid electrolyte layer 3.

[0068] The positive electrode units and the negative electrode units are alternately stacked with an offset such that one end of each unit does not coincide with the other, to produce a stack of an all-solid-state battery. Note that for the positive electrode units or the negative electrode units arranged at both ends of the stack in the stacking direction of the stack, the outermost solid electrolyte layer 3B is used as the solid electrolyte layer 3, and for the positive electrode units or the negative electrode units arranged therebetween, the interlayer solid electrolyte layer 3A is used as the solid electrolyte layer 3.

[0069] The above-described manufacturing method is for producing a parallel-type all-solid-state battery, but in a manufacturing method for a series-type all-solid-state battery, one end of the positive electrode layer 1 and one end of the negative electrode layer 2 may be stacked so as to coincide with each other, that is, without offsetting.

[0070] Furthermore, the produced laminate can be pressed collectively using a mold press, hot isostatic press (WIP), cold isostatic press (CIP), isostatic press, etc. Pressing is preferably performed while heating, and can be performed at, for example, 40 to 95°C.

[0071] The produced laminate is cut into chips using a dicing device, and then the binder is removed and fired to produce a laminate for an all-solid-state battery.

[0072] The produced laminate 20 is placed on a ceramic stand and sintered, for example, by heating to 600°C to 1000°C in a nitrogen atmosphere. The sintering time is, for example, 0.1 to 3 hours. The sintering temperature and sintering time can be appropriately changed as long as the void-forming agent is thermally decomposed and the current collector layer is not oxidized. In the case of a reducing atmosphere, sintering may be performed in, for example, an argon atmosphere or a nitrogen / hydrogen mixed atmosphere instead of a nitrogen atmosphere.

[0073] Prior to the firing step, a binder removal treatment can be carried out as a step separate from the firing step. By thermally decomposing the binder component contained in the laminate 20 before firing, it is possible to suppress rapid decomposition of the binder component during the firing process. The binder removal process is carried out, for example, in a nitrogen atmosphere at a temperature in the range of 300°C to 800°C for 0.1 to 10 hours. If a reducing atmosphere is used, firing may be carried out in, for example, an argon atmosphere or a nitrogen / hydrogen mixed atmosphere instead of a nitrogen atmosphere.

[0074] The sintered body may be placed in a cylindrical container together with an abrasive such as alumina and barrel polished. This allows the corners of the laminate to be chamfered. Alternatively, polishing by sandblasting may be used. This method is preferable because it allows only specific portions to be polished.

[0075] (Terminal formation) A first external terminal 6 and a second external terminal 7 are attached to the sintered laminate 20 (sintered body). The first external terminal 6 and the second external terminal 7 are formed so as to be in electrical contact with the positive electrode current collector 1A and the negative electrode current collector 2A, respectively. For example, they can be formed by a known method such as a sputtering method, a dipping method, a screen printing method, or a spray coating method on the positive electrode current collector 1A and the negative electrode current collector 2A exposed from the side surfaces of the sintered body. When forming the insulating film only on a predetermined portion, the insulating film is formed after masking with tape, for example.

[0076] [Second embodiment] In the all-solid-state lithium-ion secondary battery 100 according to the second embodiment, the porosity of the side margin layers 41 and 42 is set to φ m , the porosity of the solid electrolyte layer 3 is φ e The void ratio (φ m / φ e In the second embodiment, the porosity φ of the solid electrolyte layer 3 specified in the first embodiment is set to a range different from that of the first embodiment. e Instead, the porosity of the side margin layer φ m In the second embodiment, it is preferable to specify the range of the average circular area equivalent diameter (diameter) d of the voids included in the solid electrolyte layer 3 and the side margin layers 41 and 42 different from that in the first embodiment. In the second embodiment, the configuration other than the above differences is the same as that of the all-solid-state lithium-ion secondary battery 100 of the first embodiment.

[0077] <Porosity> The definition of the porosity is the same as in the first embodiment. The porosity of the side margin layer and the porosity of the solid electrolyte layer are calculated in the same manner as in the first embodiment.

[0078] In the second embodiment, the porosity of the side margin layers 41 and 42 is set to φ m , the porosity of the solid electrolyte layer 3 is φ e When the void ratio (φ m / φ e ) satisfies the following formula (4); 1.0<(φ m / φ e )≦4.0 (4)

[0079] The reason why excellent high-temperature and high-humidity cycle characteristics are obtained when the relationship as in formula (4) is satisfied is believed to be as follows. Porosity of the side margin layer φ m is the porosity of the solid electrolyte layer, φ eIf the electrode layer is designed to be larger than this, the internal stress generated by the volumetric expansion and contraction of the electrode layer during charging and discharging is dispersed and mitigated in both the solid electrolyte layer (perpendicular to the electrode layer) and the side margin layer (parallel to the electrode layer). As a result, moisture is less likely to penetrate into the solid electrolyte layer located within the laminate, more specifically between the positive electrode layer and the negative electrode layer, which contributes to the exchange of lithium ions, resulting in an all-solid-state battery with excellent high-temperature and high-humidity cycle resistance characteristics. On the other hand, the porosity of the side margin layer φ m and the porosity of the solid electrolyte layer φ e Ratio (φ m / φ e ) becomes too high, i.e., 4.0<φ m / φ e This makes it easier for moisture to penetrate from the side margin layer into the laminate, more specifically into the solid electrolyte layer located between the positive electrode layer and the negative electrode layer and contributing to the exchange of lithium ions, thereby deteriorating the high-temperature and high-humidity cycle characteristics.

[0080] In the second embodiment, the porosity ratio (φ m / φ e ) is 1.5≦(φ m / φ e )≦4.0. When the content is within this range, the all-solid-state secondary battery has excellent high-temperature and high-humidity cycle characteristics.

[0081] In the second embodiment, the porosity ratio (φ m / φ e ) is 2.0≦(φ m / φ e )≦4.0 is more preferable. When the content is within this range, the resulting all-solid-state secondary battery has even better high-temperature and high-humidity resistance cycle characteristics.

[0082] In the second embodiment, the porosity φ of the side margin layers 41 and 42 m is 0.1%≦φ m It is preferable that it is ≦20.0%. Porosity φ of the side margin layers 41 and 42 m When the temperature is within this range, the all-solid-state secondary battery has better high-temperature and high-humidity cycle characteristics.

[0083] <Average circular area equivalent diameter of voids> In the second embodiment, the average circular area equivalent diameter (diameter) d of the voids contained in the solid electrolyte layer 3 and the side margin layers 41 and 42 preferably satisfies 0.05≦d≦2 μm. Here, the average circular area equivalent diameter d is calculated by the following formula (3) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1 / 2) ×2 (3) It is calculated as follows. Here, n is preferably a number that does not cause large variations in the average equivalent circular area diameter depending on how the voids are selected. For example, as in the embodiment, n may be set to 20. In this case, when the number of voids in the SEM image is less than 20, the total area of ​​all the voids is taken as X.

[0084] When the average circular area equivalent diameter d of the voids is 0.05≦d≦2.00 μm, the all-solid-state secondary battery has better high-temperature and high-humidity cycle resistance. When the average circular area equivalent diameter d of the voids exceeds 2 μm, cracks are likely to occur in the solid electrolyte layer and the side margin layer, and the high-temperature and high-humidity cycle resistance is deteriorated.

[0085] The average circular area equivalent diameter in the examples was calculated by converting the SEM images of the solid electrolyte layer and the side margin layer into monochrome images and binarizing them using the method used to calculate the porosity described above, obtaining the total area X of a total of 20 void portions (black), and then using formula (3).

[0086] (Terminal) In the second embodiment, the first external terminal 6 and the second external terminal 7 of the all-solid-state lithium-ion secondary battery 100 can have the same configuration as in the first embodiment.

[0087] (protective layer) In the second embodiment, the all-solid-state lithium-ion secondary battery 100 may have a protective layer (not shown) that electrically, physically, and chemically protects the laminate 20 and the terminals on the outer periphery of the laminate 20. The configuration and material of the protective layer are preferably the same as those in the first embodiment.

[0088] (Manufacturing method of all-solid-state lithium-ion secondary battery) The manufacturing method of the all-solid-state lithium-ion secondary battery 100 in the second embodiment is preferably the same as the manufacturing method of the solid-state lithium-ion secondary battery 100 in the first embodiment.

[0089] The first and second embodiments of the present invention have been described above in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES

[0090] [Example 1A] (Preparation of paste for solid electrolyte layer) Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 To 100 parts of the powder, 100 parts of ethanol and 200 parts of toluene were added as a solvent in a ball mill and wet mixed. Then, 16 parts of polyvinyl butyral binder as a binder, 4.8 parts of benzyl butyl phthalate as a plasticizer, and 1 part of nylon fine particles with an average particle size of 1 μm as a void-forming agent were added and mixed to prepare a solid electrolyte layer paste. The paste for the solid electrolyte layer was formed into sheets by a doctor blade method using a PET film as a substrate to obtain an outermost solid electrolyte layer sheet and an interlayer solid electrolyte layer sheet, each of which had a thickness of 15 μm.

[0091] (Preparation of paste for side margins) Li 1.3 Al0.3 Ti 1.7 (PO 4 ) 3 To 100 parts of the powder, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added, and 0.7 parts of nylon microparticles with an average particle size of 1 μm were added as a void-forming agent. The mixture was mixed and dispersed to prepare a paste for the side margin.

[0092] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive electrode active material layer and the paste for the negative electrode active material layer are Li 3 V 2 (PO 4 ) 3 After mixing these in a predetermined weight ratio, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added to 100 parts of this powder, and the mixture was mixed and dispersed to prepare a paste for a positive electrode active material layer and a paste for a negative electrode active material layer.

[0093] (Preparation of Positive Electrode Current Collector Paste and Negative Electrode Current Collector Paste) The paste for the positive and negative current collectors contains Cu and Li as current collectors. 3 V 2 (PO 4 ) 3 After mixing them in a volume ratio of 80:20, 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added to 100 parts of this powder, and the mixture was mixed and dispersed to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.

[0094] (Preparation of electrode unit) The positive electrode unit and the negative electrode unit were prepared as follows. On the interlayer solid electrolyte layer sheet, a paste for a positive electrode active material was printed by screen printing to a thickness of 5 μm. Next, the printed paste for a positive electrode active material was dried at 80 ° C. for 5 minutes, and a paste for a current collector was printed thereon to a thickness of 5 μm by screen printing. Next, the printed paste for a positive electrode current collector was dried at 80 ° C. for 5 minutes, and a paste for a positive electrode active material was printed again thereon to a thickness of 5 μm by screen printing and dried. Then, a paste for a side margin layer was screen printed on the region of the solid electrolyte layer sheet other than the positive electrode layer, and dried to form a side margin layer having a height approximately equal to that of the electrode layer. Next, the PET film was peeled off. In this way, a positive electrode unit was obtained in which a positive electrode layer in which a positive electrode active material layer / a positive electrode current collector layer / a positive electrode active material layer were laminated in this order on the main surface of the interlayer solid electrolyte layer, and a positive electrode side margin layer arranged in contact with the side surface of the positive electrode layer was formed on the outer periphery. Using a similar procedure, a negative electrode unit was obtained in which a negative electrode layer in which a negative electrode active material layer / a negative electrode current collector layer / a negative electrode active material layer were laminated in this order on the main surface of the solid electrolyte layer and a negative electrode side margin layer 42 was formed on the outer periphery of the negative electrode layer and arranged in contact with the side surface of the positive electrode layer.

[0095] (Preparation of Laminate) Five solid electrolyte layer sheets for the outermost solid electrolyte layer were stacked, and 50 electrode units (25 positive electrode units, 25 negative electrode units) were stacked alternately on top of them with the interlayer solid electrolyte interposed. At this time, each unit was stacked with a shift so that the collector paste layer of the odd-numbered electrode units extended only to one end surface, and the collector paste layer of the even-numbered electrode units extended only to the opposite end surface. Six solid electrolyte layer sheets for the outermost solid electrolyte layer were stacked on top of the stacked units. After that, this was molded by thermocompression bonding, and then cut to produce a laminated chip. Then, the laminated chips were simultaneously fired to obtain a laminate. For simultaneous firing, the temperature was raised to 840°C at a heating rate of 200°C / hour in a nitrogen atmosphere, and the temperature was maintained for 2 hours, and the firing was allowed to cool naturally.

[0096] (Production and evaluation of all-solid-state secondary batteries) A first external terminal and a second external terminal were attached to the sintered laminate (sintered body) by a known method to prepare an all-solid-state secondary battery. The first external terminal and the second external terminal were sandwiched by spring probes so as to face each other, and a charge / discharge test was performed to measure the initial discharge capacity and the capacity retention rate after 500 cycles of the all-solid-state secondary battery. The measurement conditions were a current of 20 μA during both charging and discharging, and a cut-off voltage of 1.6 V and 0 V during charging and discharging, respectively. The results are shown in Table 1. The capacity during the first discharge was taken as the initial discharge capacity. The capacity retention rate was calculated by dividing the discharge capacity at the 500th cycle by the initial discharge capacity. The results are shown in Table 1.

[0097] Furthermore, the average porosity of the solid electrolyte layer and the side margin layer of the sintered laminate (sintered body) was calculated by the method described above, and was found to be 1.0% and 0.7%, respectively. The results are shown in Table 1.

[0098] In addition, in SEM images of the cross sections of the solid electrolyte layer and the side margin layer of the sintered laminate (sintered body), the average circular area equivalent diameter was calculated by the above-mentioned method, and the void diameter was 0.6 μm. The results are shown in Table 1.

[0099] [Table 1]

[0100] [Example 2A to Example 22A] In each of Examples 2A to 22A, all-solid-state secondary batteries were produced in the same manner as in Example 1A, except that the porosity was adjusted by changing the amount of nylon fine particles, which is a void-forming material, added in the preparation of the paste for the solid electrolyte layer and the paste for the side margin. The amount of nylon microparticles added is shown in Table 2.

[0101] [Comparative Example 1A to Comparative Example 19A] In Comparative Example 1A to Comparative Example 19A, all-solid-state secondary batteries were produced in the same manner as in Example 1A, except that the porosity was adjusted by changing the amount of nylon fine particles, which is a void-forming material, added in the preparation of the paste for the solid electrolyte layer and the paste for the side margin. The amount of nylon microparticles added is shown in Table 2.

[0102] [Example A23 to Example 26A] In each of Examples 23A to 26A, all-solid-state secondary batteries were produced in the same manner as in Example 4A, except that the particle diameter of the nylon fine particles serving as the void-forming material was changed to adjust the size of the voids. The particle sizes of the nylon fine particles were, respectively, 0.2 μm in Example 23A, 2.0 μm in Example 24A, 3.0 μm in Example 25A, and 5.0 μm in Example 26A. The amount of nylon microparticles added is shown in Table 2.

[0103] [Table 2]

[0104] Based on Table 1, the cycle characteristics were 90% or more for Examples 1A, 4A, 5A, 7A, 10A, 11A, 23A, and 24A, and the porosity ratios (φ m / φ e ) is in the range of 0.6≦(φ m / φ e )≦0.87.

[0105] Further, based on Table 1, when the cycle characteristics are expanded to 89% or more, Examples 2A, 8A, and 13A are added, and the void ratio (φ m / φ e ) is in the range of 0.6≦(φ m / φ e )≦0.90.

[0106] Further, based on Table 1, if the cycle characteristics are expanded to 88% or more, Examples 6A, 12A, and 14A are further added, and the void ratio (φ m / φ e ) is in the range of 0.6≦(φ m / φ e )≦0.97.

[0107] Furthermore, based on Table 1, if the cycle characteristics are expanded to 87% or more, Examples 9A and 15A are added. m / φ e ) is in the range of 0.6≦(φ m / φ e )≦0.99.

[0108] Based on Table 1, the cycle characteristics were 90% or more for Examples 1A, 4A, 5A, 7A, 10A, 11A, 23A, and 24A, as described above, and the porosity φ of the solid electrolyte layer of these e The range is 1.0≦φ e ≦10.7.

[0109] In addition, when the cycle characteristics are expanded to 89% or more, as described above, Examples 2A, 8A, and 13A are added, and the porosity φ of the solid electrolyte layer after the addition of Examples 2A, 8A, and 13A is e The range is 1.0≦φ e ≦11.9.

[0110] [Example 1-1B] (Preparation of paste for solid electrolyte layer) Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3To 100 parts of the powder, 100 parts of ethanol and 200 parts of toluene were added as a solvent and wet-mixed in a ball mill. Then, 16 parts of a polyvinyl butyral binder as a binder, 4.8 parts of benzyl butyl phthalate as a plasticizer, and 4.5 parts of nylon fine particles with an average particle size of 1 μm as a void-forming agent were added and mixed to prepare a paste for the solid electrolyte layer. The paste for the solid electrolyte layer was formed into sheets by a doctor blade method using a PET film as a substrate to obtain an outermost solid electrolyte layer sheet and an interlayer solid electrolyte layer sheet, each of which had a thickness of 15 μm.

[0111] (Preparation of paste for side margins) Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 To 100 parts of the powder, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added, and 5.0 parts of nylon microparticles with an average particle size of 1 μm as a void-forming agent were added, and the mixture was mixed and dispersed to prepare a paste for the side margin layer.

[0112] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive electrode active material layer and the paste for the negative electrode active material layer are Li 3 V 2 (PO 4 ) 3 To 100 parts of this powder, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added, and the mixture was mixed and dispersed to prepare a paste for a positive electrode active material layer and a paste for a negative electrode active material layer.

[0113] (Preparation of Positive Electrode Current Collector Paste and Negative Electrode Current Collector Paste) The paste for the positive and negative current collectors contains Cu and Li as current collectors. 3 V 2 (PO 4 ) 3After mixing them in a volume ratio of 80:20, 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added to 100 parts of this powder, and the mixture was mixed and dispersed to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.

[0114] (Preparation of electrode unit) The positive electrode unit and the negative electrode unit were prepared as follows. On the interlayer solid electrolyte layer sheet, a paste for a positive electrode active material was printed by screen printing to a thickness of 5 μm. Next, the printed paste for a positive electrode active material was dried at 80 ° C. for 5 minutes, and a paste for a current collector was printed thereon to a thickness of 5 μm by screen printing. Next, the printed paste for a positive electrode current collector was dried at 80 ° C. for 5 minutes, and a paste for a positive electrode active material was printed again thereon to a thickness of 5 μm by screen printing and dried. Then, a paste for a side margin layer was screen printed on the region of the solid electrolyte layer sheet other than the positive electrode layer, and dried to form a side margin layer having a height approximately equal to that of the electrode layer. Next, the PET film was peeled off. In this way, a positive electrode unit was obtained in which a positive electrode layer in which a positive electrode active material layer / a positive electrode current collector layer / a positive electrode active material layer were laminated in this order on the main surface of the interlayer solid electrolyte layer, and a positive electrode side margin layer arranged in contact with the side surface of the positive electrode layer was formed on the outer periphery. Using a similar procedure, a negative electrode unit was obtained in which a negative electrode layer in which a negative electrode active material layer / a negative electrode current collector layer / a negative electrode active material layer were laminated in this order on the main surface of the solid electrolyte layer and a negative electrode side margin layer was formed on the outer periphery of the negative electrode layer and in contact with the side surface of the negative electrode layer.

[0115] (Preparation of Laminate) Five solid electrolyte layer sheets for the outermost solid electrolyte layer were stacked, and 50 electrode units (25 positive electrode units, 25 negative electrode units) were stacked alternately on top of them with the interlayer solid electrolyte interposed. At this time, each unit was stacked with a shift so that the collector paste layer of the odd-numbered electrode units extended only to one end surface, and the collector paste layer of the even-numbered electrode units extended only to the opposite end surface. Six solid electrolyte layer sheets for the outermost solid electrolyte layer were stacked on top of the stacked units. After that, this was molded by thermocompression bonding, and then cut to produce a laminated chip. Then, the laminated chips were simultaneously fired to obtain a laminate. For simultaneous firing, the temperature was raised to 840°C at a heating rate of 200°C / hour in a nitrogen atmosphere, and the temperature was maintained for 2 hours, and the firing was allowed to cool naturally.

[0116] (Production and evaluation of all-solid-state secondary batteries) A first external terminal and a second external terminal were attached to the sintered laminate (sintered body) by a known method to prepare an all-solid-state secondary battery. The first external terminal and the second external terminal were sandwiched by a spring probe so as to face each other, and a charge / discharge test was performed under conditions of a temperature of 40°C and a humidity of 93%, to measure the initial discharge capacity and the capacity retention rate after 100 cycles of the all-solid-state secondary battery. The measurement conditions were a current of 20 μA during both charging and discharging, and a cut-off voltage of 1.6 V and 0 V during charging and discharging, respectively. As a result, the cycle characteristic was 70%. The capacity during the first discharge was taken as the initial discharge capacity. The capacity retention rate was calculated by dividing the discharge capacity at the 100th cycle by the initial discharge capacity. The results are shown in Table 3.

[0117] The porosity of the solid electrolyte layer and the side margin layer of the sintered laminate (sintered body) was calculated by the method described above and was found to be 4.5% and 5%, respectively. The results are shown in Table 3.

[0118] Furthermore, in SEM images of the cross sections of the solid electrolyte layer and the side margin layer of the sintered laminate (sintered body), the average equivalent circular area diameter was calculated by the above-mentioned method and was found to be 0.5 μm. The results are shown in Table 3.

[0119] [Table 3]

[0120] [Examples 1-2B to 1-6B, Comparative Examples 1-1B to 1-2B] In Examples 1-2B to 1-6B and Comparative Examples 1-1B to 1-2B, all-solid-state secondary batteries were produced in the same manner as in Example 1-1B, except that the porosity was adjusted by changing the amount of nylon fine particles having an average particle size of 1 μm added in the preparation of the solid electrolyte layer paste and the side margin layer paste. The amount of nylon microparticles added is shown in Table 4.

[0121] [Table 4]

[0122] As shown in Table 3, the cycle characteristics at high temperature and high humidity (temperature 40° C., humidity 93%) were less than 50% for Comparative Example 1-1B and Comparative Example 1-2B, while the porosity ratio (φ m / φ e ) is 1.1≦(φ m / φ e In Examples 1-1B to 1-6B, the porosity ratio (φ) was 70% or more, which was in the range of ≦4.0. m / φ e ) is 1.5≦(φ m / φ e In Examples 1-3B to 1-6B, the void ratio (φ) is in the range of 75% or more, and the void ratio (φ) is in the range of ≦4.0. m / φ e ) is 2.0≦(φ m / φ e In Examples 1-4B to 1-6B, in which the range was ≦4.0, the value was 80% or more.

[0123] [Examples 2-1B to 2-20B, Comparative Examples 2-1B to 2-8B] In Example 2-1B to Example 2-20B and Comparative Example 2-1B to Comparative Example 2-8B, all-solid-state secondary batteries were produced in the same manner as in Example 1-1B, except that the porosity was adjusted by changing the amount of nylon fine particles having an average particle size of 1 μm in the preparation of the solid electrolyte layer paste and the side margin layer paste. The amount of nylon microparticles added is shown in Table 5. The evaluation results of the all-solid-state secondary batteries are shown in Table 6.

[0124] [Table 5]

[0125] [Table 6]

[0126] As shown in Table 6, the cycle characteristics at high temperature and high humidity (temperature 40° C., humidity 93%) were less than 50% in Comparative Examples 2-1B to 2-8B, whereas the porosity φ m 0.1≦φ m In Examples 2-1B to 2-20B, which are in the range of ≦20, the porosity φ of the side margin layer was 60% or more. m φ is 1 or less m In Examples 2-5B to 2-12B, which are in the range of ≦10, the value was 72% or more.

[0127] [Examples 3-1B to 3-4B, Comparative Example 3-1B] In Examples 3-1B to 3-4B and Comparative Example 3-1B, all-solid-state secondary batteries were produced in the same manner as in Example 1-1B, except that in preparing the paste for the solid electrolyte layer and the paste for the side margin layer, the average particle diameters of the nylon fine particles added as a void-forming agent were set to 0.2 μm, 2.0 μm, 0.1 μm, 3.0 μm, and 8.0 μm, respectively, to adjust the average circular area equivalent diameter. The amount of nylon microparticles added is shown in Table 7. The evaluation results of the all-solid-state secondary batteries are shown in Table 8.

[0128] [Table 7]

[0129] [Table 8]

[0130] As shown in Table 8, the cycle characteristics at high temperature and high humidity (temperature 40°C, humidity 93%) were less than 60% for Comparative Example 3-1B, whereas the cycle characteristics at high temperature and high humidity (temperature 40°C, humidity 93%) were 70% or more for all of Examples 3-1B to 3-4B in which the average circular area equivalent diameter d was 0.05≦d≦2.00 μm. In particular, the cycle characteristics at high temperature and high humidity (temperature 40°C, humidity 93%) were 78% or more for Examples 3-1B to 3-2B in which the average circular area equivalent diameter d was 0.1≦d≦1 μm. [Explanation of symbols]

[0131] 1 Positive electrode layer 1A positive electrode current collector 1B Cathode active material layer 2. Negative electrode layer 2A negative electrode current collector 2B Negative electrode active material layer 3 Solid electrolyte layer 3A interlayer solid electrolyte layer 3B Outermost solid electrolyte layer 41 Positive electrode side margin layer 42 Negative electrode side margin layer 6 First external terminal 7 Second external terminal 20 Laminate 100 All-solid-state secondary battery

Claims

1. a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer; a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer; a solid electrolyte layer including a solid electrolyte; a side margin layer arranged adjacent to and around the positive electrode layer and the negative electrode layer, the side margin layer being made of a solid electrolyte; the positive electrode layer and a side margin layer disposed around the positive electrode layer, and the negative electrode layer and a side margin layer disposed around the negative electrode layer are alternately stacked with the solid electrolyte layer interposed therebetween to form a laminate; The porosity of the side margin layer is φ m , the porosity of the solid electrolyte layer is φ e When the void ratio (φ m / φ e ) satisfies the following formula (1): 0.5≦(φ) m / φ e )<1.0 ・・・・ (1)

2. 2. The all-solid-state secondary battery according to claim 1, wherein the solid electrolyte contained in the side margin layer is the same as the solid electrolyte contained in the solid electrolyte layer.

3. The porosity ratio (φ m / φ e 3. The all-solid-state secondary battery according to claim 1, wherein 0.6≦(φ) m / φ e )<1.0 ・・・・ (2)

4. The porosity φ of the solid electrolyte layer e is 1.0%≦φ e The all-solid-state secondary battery according to any one of claims 1 to 3, wherein the conductivity is ≦25.0%.

5. The all-solid-state secondary battery according to any one of claims 1 to 4, wherein an average circular area equivalent diameter d of voids included in the solid electrolyte layer and the side margin layer is 0.1≦d<2.0 μm; Here, the average circular area equivalent diameter d is calculated by the following formula (3) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1/2) ×2 ・・・(3) It is calculated as follows.

6. a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer; a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer; a solid electrolyte layer including a solid electrolyte; a side margin layer arranged adjacent to and around the positive electrode layer and the negative electrode layer, the side margin layer being made of a solid electrolyte; the positive electrode layer and a side margin layer disposed around the positive electrode layer, and the negative electrode layer and a side margin layer disposed around the negative electrode layer are alternately stacked with the solid electrolyte layer interposed therebetween to form a laminate; The porosity of the side margin layer is φ m , the porosity of the solid electrolyte layer is φ e When the void ratio (φ m / φ e ) satisfies the following formula (4): 1.0<(φ) m / φ e )≦4.0 ・・・・ (4)

7. The all-solid-state secondary battery according to claim 6 , wherein the solid electrolyte contained in the side margin layer is the same as the solid electrolyte contained in the solid electrolyte layer.

8. The porosity φ of the side margin layer m is 0.1%≦φ m The all-solid-state secondary battery according to claim 6 or 7, wherein the content is ≦20.0%.

9. The all-solid-state secondary battery according to any one of claims 6 to 8, wherein an average circular area equivalent diameter d of voids included in the solid electrolyte layer and the side margin layer is 0.05≦d≦2.00 μm; Here, the average circular area equivalent diameter d is calculated by the following formula (3) when the total area of ​​n voids in the SEM image is X: d={X / (n×π)} (1/2) ×2 ・・・(3) It is calculated as follows.

Citation Information

Patent Citations

  • Laminate including active material layer and solid electrolyte layer, and all solid lithium secondary battery using it

    JP2007005279A

  • Lithium ion conductive solid electrolyte and its manufacturing method

    JP2007294429A

  • All-solid type secondary battery

    JP2014192041A

  • All-solid battery and manufacturing method thereof

    JP2018166020A

  • Solid electrolyte structure for all-solid-state battery, all-solid-state battery, and their production methods

    WO2008059987A1